Melatonin mends adverse temporal effects of bright light at night partially independent of its effect on stress responses in captive birds. (1st February 2020) - Malek, I.; Haim, A.; Izhaki, I.
ABSTRACT: Ecological artificial light at night (ALAN) has been increasingly associated with negative effects on the behavior and ecology of wild birds. However, the impacts of short-term bright ALAN on the temporal biology of companion animals and the underlying mediating mechanism are unknown. We evaluated impacts of 1X60-min/middle night ALAN (200 lux, λDominant  = 460 nm) nightly with or without melatonin administration on growth performance, reproductive capacity, food and water intake, and stress responses in Australian budgerigars ( Melopsittacus undulatus ) under captivity. 36 birds were housed in pairs under natural photoperiod and were equally divided into three groups: control, natural conditions; ALAN, control + ALAN; and melatonin, ALAN + melatonin in the drinking water during the dark period. Birds were regularly monitored for body mass, egg production, and hatchability over four months. Food intake, water consumption, and daily rhythm of fecal corticosterone were also evaluated. ALAN increased mass gain, food intake, water consumption, and drastically decreased reproductive capacity, whereas stress responses were markedly augmented. Melatonin restored food and water intake to control levels but partly reversed mass gain. Melatonin failed to ameliorate the impaired reproductive capacity despite reducing the stress responses to basal levels. These results suggest that the ALAN-induced negative impacts cannot be attributed solely to direct effects of melatonin suppression or/and exacerbated stress responses and the involvement of other photoperiodic pathway components warrant further studies. Finally, the results of our study may be of importance for improving the housing conditions of companion animals at least as concern bright ALAN exposures.